m6A Regulator-Mediated Methylation Modification Patterns and Characterisation of Tumour Microenvironment Infiltration in Non-Small Cell Lung Cancer - Fan Y; Zhou Y; Lou M; Li X; Zhu X; Yuan K (Dove Medical Press, 2022)
Yongfei Fan,1 Yong Zhou,1 Ming Lou,1 Xinwei Li,2 Xudong Zhu,1 Kai Yuan1,3 1Department of Thoracic Surgery, The Affiliated Changzhou No. 2 People's Hospital of Nanjing Medical University, Changzhou, People's Republic of China; 2Department of Gastroenterology, Affiliated Cancer Hospital of Bengbu Medical College, Bengbu, People's Republic of China; 3Heart and Lung Disease Laboratory, The Affiliated Changzhou No. 2 People's Hospital of Nanjing Medical University, Changzhou, People's Republic of ChinaCorrespondence: Kai Yuan, Department of Thoracic Surgery, The Affiliated Changzhou No. 2 People's Hospital of Nanjing Medical University, No. 29 Xinglong Lane, Changzhou, 213003, Jiangsu Province, People's Republic of China, Tel +86-13915890721, Email yuankai1978@163.comPurpose: The role of RNA N6-methyladenosine (m6A) modification in the progression of multiple tumours and the tumour microenvironment (TME) has been progressively demonstrated and promises a new direction for tumour therapy. However, there have been no reports on systematic analyses of RNA m6A modification in TME in non-small cell lung cancer (NSCLC).Patients and Methods: In this study, we used unsupervised cluster analysis to identify three m6A modification patterns of 28 m6A regulators and three m6A gene signature subgroups of commonly differentially expressed genes (co-DEGs) in the three m6A modification patterns. Quantifying these subtypes using the ssGSEA and ESTIMATE algorithms to characterise the tumour immune microenvironment (TIME) in NSCLC. Based on the principal component analysis (PCA), we used co-DEGs to construct m6A scores to analyse the characteristics of m6A modifications in individual patients and assessed the practical clinical utility of m6A scores using a nomogram for survival prediction.Results: A total of 28 m6A regulators in 1210 NSCLC samples were mainly enriched in RNA modification and metabolic biological processes. The three following m6A modification patterns were identified based on the role of the 28 m6A regulators in TME: immune inflammation, immune evasion and immune desert. The m6A scores calculated based on co-DEGs in these modification patterns were significantly positively correlated with immune infiltration and significantly negatively correlated with tumour mutational burden (TMB). Survival was significantly better in the high-m6A-score group than in the low-m6A-score group, and the m6A score could be used as an independent favourable prognostic factor. In addition, assessment of both immune checkpoint inhibitors (ICIs) and immunophenoscore (IPS) revealed a better immunotherapeutic effect in the high-m6A-score group.Conclusion: The modification characteristics of 28 m6A regulators in the TIME of NSCLC were analysed from a comprehensive to an individual basis, which may facilitate the development of more effective clinical immunotherapeutic strategies.Graphical Abstract: Keywords: immunophenotype, immunotherapy, m6A modification, non-small cell lung cancer, tumour microenvironment